Antimicrobial activity, phenolic content and cytotoxicity of medicinal plant extracts used for treating dermatological diseases and wound healing in KwaZulu-Natal, South Africa - Shanaz Ghuman; Bhekumthetho Ncube; Jeffrey F Finnie; Lyndy Joy McGaw; Roger M Coopoosamy; Johannes Van Staden (Frontiers Media S.A., 2016)
Medicinal plants used for wound healing and skin diseases are the key to unlocking the doors to combating problematic skin diseases as resistance of pathogens to pharmaceuticals and allopathic management continues to increase. The study aimed at investigating the antimicrobial efficacies, phenolic content and cytotoxicity effects of eleven medicinal plant extracts commonly used for treating skin conditions and wound healing in traditional medicine within KwaZulu-Natal. Eleven plant species were separated into different plant parts (bulbs, roots, leaves) and extracted with different solvents. The extracts were assessed for antimicrobial activity against six Gram-positive and seven Gram-negative bacterial strains and four fungi commonly associated with skin conditions using disc diffusion and microdilution techniques. The aqueous methanolic extracts were screened for phenolic content while cytotoxicity tests were performed on all extracts using the brine shrimp lethality and tetrazolium-based colorimetric (MTT) assays. Extracts from Aloe ferox, A. arborescens and Hypericum aethiopicum were the most active against almost all of the tested bacterial and fungal strains. All plant species exhibited some degree of antimicrobial activity. Total phenolic levels, flavonoids and tannins were also higher for A. ferox, followed by A. arborescens and H. aethiopicum respectively. The cytotoxicity results of all plant extracts were in the range of 90-100% survival after 24 h in the Brine shrimp assay. Extracts considered lethal would demonstrate > 50% shrimp death. The MTT cytotoxicity test yielded LC50 values of > 1 mg/mL on all extracts indicating that they are not cytotoxic. The observed antimicrobial efficacy demonstrated by some plant species and the general lack of cytotoxic effects on all the tested extracts presents some promising and beneficial aspects of these medicinal plant extracts in the treatment of skin diseases and wound healing. The two Aloe species and H. aethiopicum were among the best extracts that exhibited consistently good antimicrobial activity and warrants further investigations and possible isolation of bioactive principles.